PENERAPAN PROSEDUR LASHING MUATAN PETI KEMAS UNTUK MELINDUNGI MUATAN DI KM.TANTO BERKAT - Eghia Surya (Jurnal 7 Samudra, 2024)
Lashing procedures applied at KM. Tanto Berkat successfully protect container cargo from damage and shifting during shipping, complying with international safety standards. Implementation of proper lashing techniques, use of quality equipment, and adequate crew training are the main factors in the success of the lashing system. This research recommends that lashing procedures be continuously optimized, with a focus on training, maintenance, and regular evaluation to ensure maximum load protection. In addition, close collaboration between ship management and port operators in regular reviews of lashing procedures and the implementation of dynamic safety standards in accordance with developments in international regulations also play an important role in maintaining system reliability. This research also underscores the importance of adapting to changing weather and sea conditions, which can affect cargo stability during shipping. Taking these factors into account, other recommendations resulting from this research include increasing the frequency of pre-cruise inspections and adapting lashing techniques according to the size and type of cargo. The overall approach aims to increase the effectiveness of the lashing system, ensure shipping safety, and protect the integrity of the cargo. during sea voyages.